Decline of German Historicism: Friedrich Meinecke's theory of Historical Value - Zhang, Yi (Historical Journal, 2025)
German Historism, a prominent historical school that flourished in Germany from the late 19th to the early 20th century, exerted considerable influence within the Western historical community. Despite its prominence, the reasons for the decline of this once-thriving school remain largely unexplained. Although there is an abundance of research on Friedrich Meinecke, the last leading figure of the German Historians, these studies have not effectively connected his historical ideas to the broader context of the school's decline. This oversight has led to a disconnection between the historical thought of the past and the historical currents of their times, imposing significant limitations on the research. This article, therefore, delves into the heart of Meinecke's historical value theory. It aims to conduct a qualitative analysis of the factors contributing to the decline of German Historism. This is achieved by examining the intertextual connections between Meinecke's work and the broader historiographical landscape, employing a range of historical theoretical tools, including the Philosophy of History, Comparative Historical Analysis, and Conceptual History.